Association between left ventricular diastolic dysfunction and severity of chronic obstructive pulmonary disease (Clinics, 2013)
OBJECTIVES: The prevalence of electrocardiographic and echocardiographic abnormalities in chronic obstructive pulmonary disease according to disease severity has not yet been established. The aim of this study was to assess the prevalence of electrocardiographic and echocardiographic abnormalities in chronic obstructive pulmonary disease patients according to disease severity. METHODS: The study included 25 mild/moderate chronic obstructive pulmonary disease patients and 25 severe/very severe chronic obstructive pulmonary disease patients. All participants underwent clinical evaluation, spirometry and electrocardiography/echocardiography. RESULTS: Electrocardiography and echocardiography showed Q-wave alterations and segmental contractility in five (10%) patients. The most frequent echocardiographic finding was mild left diastolic dysfunction (88%), independent of chronic obstructive pulmonary disease stage. The proportion of right ventricular overload (p